STRATEGI FUNDRISING, PENGELOLAAN DAN PENGEMBANGAN WAKAF UANG DI DOMPET DHUAFA JAWA TIMUR - Anifah, Siti (Commodity : Jurnal Perbankan dan Keuangan Islam, 2025)
Cash waqf holds significant potential in strengthening the national Islamic economic system. However, its realization has yet to reach an optimal level. One of the key strategic factors in the development of cash waqf lies in the performance of nazhir (waqf managers). This study aims to analyze the fundraising strategies, management, and development of cash waqf as implemented by Dompet Dhuafa East Java. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings reveal that cash waqf fundraising activities at Dompet Dhuafa East Java largely depend on campaigns and programs initiated by the Dompet Dhuafa central office. This dependency also extends to the management and development of waqf programs. Several challenges were identified, including low public literacy on cash waqf, limited socialization efforts, and the lack of comprehensive information dissemination regarding waqf programs. These issues have led to a low level of public trust in cash waqf instruments, resulting in significantly lower fundraising outcomes compared to Zakat, Infaq, and Sadaqah (ZIS). To enhance the development of cash waqf, strategic efforts should involve collaboration with formal and non-formal educational institutions, religious leaders, influencers, and various societal elements, while optimizing the use of social media platforms. Furthermore, regular implementation of focus group discussions (FGDs) and seminars, both online and offline, is essential to increase public awareness. Additionally, capacity building for waqf management can be achieved through continuous guidance and supervision from regulatory bodies, aimed at fostering trustworthy, professional, and accountable nazhir. Through these efforts, public awareness and participation in cash waqf via Dompet Dhuafa East Java are expected to improve significantly.